Basin-scale distribution of harbour porpoises in the Baltic Sea provides basis for effective conservation actions. (October 2018) - Carlén, Ida; Thomas, Len; Carlström, Julia; Amundin, Mats; Teilmann, Jonas; Tregenza, Nick; Tougaard, Jakob; Koblitz, Jens C.; Sveegaard, Signe; Wennerberg, Daniel; Loisa, Olli; Dähne, Michael; et al.
Abstract: Knowledge on spatial and seasonal distribution of species is crucial when designing protected areas and implementing management actions. The Baltic Proper harbour porpoise ( Phocoena phocoena ) population is critically endangered, and its distribution is virtually unknown. Here, we used passive acoustic monitoring and species distribution models to describe the spatial and seasonal distribution of harbour porpoises in the Baltic Proper. Porpoise click detectors were deployed over a systematic grid of 297 stations in eight countries from April 2011 through July 2013. Generalized additive models were used to describe the monthly probability of detecting porpoise clicks as a function of spatially-referenced covariates and time. During the reproductive season, two main areas of high probability of porpoise detection were identified. One of those areas, situated on and around the offshore banks in the Baltic Proper, is clearly separated from the known distribution range of the Belt Sea population during breeding season, suggesting this is an important breeding ground for the Baltic Proper population. We commend the designation of this area as a marine protected area and recommend Baltic Sea countries to also protect areas in the southern Baltic Sea and the Hanö Bight where additional important harbour porpoise habitats were identified. Further conservation measures should be carried out based on analyses of overlap between harbour porpoise distribution and potentially harmful anthropogenic activities. Our study shows that large-scale systematic monitoring using novel techniques can give important insights on the distribution of low-density populations, and that international cooperation is pivotal when studying transnationally migratory species. Highlights: Results support the existence of a separate Baltic Proper porpoise population. An important breeding site for the endangered Baltic Proper porpoise is identified. Population distribution patterns give a solid base for designating protected areas. Large-scale monitoring can give insights on distribution of low-density populations. International cooperation is key for studies of transnationally migratory species.